West Texas Intermediate and Brent Spread during Organization of the Petroleum Exporting Countries Supply Disruptions - Omar, Ayman M.A. (International Journal of Energy Economics and Policy, 2015)
This paper investigates the price spread between West Texas Intermediate and Brent during periods of supply disruptions. Using a sample of 50 events of Organization of the Petroleum Exporting Countries (OPEC) - related unplanned upstream production outages, this paper documents a statistically significant tightening in the price differential. The finding is robust even after accounting for 22 OPEC - related political conflicts, 104 extreme weather conditions in the Atlantic basin, and the period of infrastructural bottlenecks in and around the Cushing, Oklahoma. The result is further confirmed when examining the spread between Light Louisiana sweet and Brent. These findings suggest the need to hedge against such risks and give rise to speculative trading which can be facilitated using the vibrant paper markets. Keywords: Crude Oil, Benchmarks, Organization of the Petroleum Exporting Countries, Supply Disruptions JEL Classifications: G12, Q34, Q41